Pengaruh Brand Image, Product Quality, dan Price Discount Terhadap Impulse Buying pada Produk Make Over di Kota Surabaya - Miftachul Jannah; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine and analyze the effect of brand image, product quality and price discount on impulse buying. The method used in this research is a quantitative associative method. The data in this research was tested using validity tests, reliability tests, classic assumption tests, multiple linear regression tests and hypothesis tests analyze using the IBM SPSS Statistics 24 application. The data collection technique in this study was a questionnaire and the sampling technique in this study was purposive sampling. The criteria used were women aged between 20 and 49, living in the city of Surabaya and who purchased Make Over products. The results of this study indicate that, in part, the variables brand image, product quality and price discount have a positive and significant effect on impulse buying. In addition, other results also show that simultaneously the variables brand image, product quality and price discount have a positive and significant effect of 77.7% on the impulse purchase of Make Over products in the city of Surabaya.